2017
DOI: 10.12973/iji.2017.1025a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Critical Thinking Skills and Writing Skills through the Variation in Non-Traditional Writing Task

Abstract: The research aims to identify the impacts of embedding non-traditional writing tasks within the course of modern physics conducted to the students of Physics Education and Physics Study Programs. It employed a quasi-experimental method with the pretest-posttest control group design. The used instruments were tests on conceptual mastery, tests on critical thinking skills, and a rubric of writing assessment. The data were analyzed by determining the percentages of average normalized gains, Cohen's d, and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 19 publications
3
19
0
3
Order By: Relevance
“…The research findings show that writing-to-learn activities provided an improvement in the levels of critical thinking skill demonstrated by the prospective Social Studies teachers; also, a significant difference emerged in their critical thinking dispositions. The result is parallel to many other studies in the literature (Burhanuddin & Ibrahim, 2019;Hobson & Schafermeyer, 1994;Giroux, 1978;Gupta et al, 2015;Hooey & Bailey, 2005;Nejmaoui, 2019;Quitadamo & Kurtz, 2007, Sinaga & Feranie, 2017Stephenson & Sadler-McKnight, 2016;Walp, 2013). The first reason for this change that occurs in both the critical thinking dispositions and the critical thinking skills is that the writing-to-learn activities arouse curiosity about the subject and lead the prospective teachers to think and do more in-depth research.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The research findings show that writing-to-learn activities provided an improvement in the levels of critical thinking skill demonstrated by the prospective Social Studies teachers; also, a significant difference emerged in their critical thinking dispositions. The result is parallel to many other studies in the literature (Burhanuddin & Ibrahim, 2019;Hobson & Schafermeyer, 1994;Giroux, 1978;Gupta et al, 2015;Hooey & Bailey, 2005;Nejmaoui, 2019;Quitadamo & Kurtz, 2007, Sinaga & Feranie, 2017Stephenson & Sadler-McKnight, 2016;Walp, 2013). The first reason for this change that occurs in both the critical thinking dispositions and the critical thinking skills is that the writing-to-learn activities arouse curiosity about the subject and lead the prospective teachers to think and do more in-depth research.…”
Section: Discussionsupporting
confidence: 87%
“…The more we think about a subject, the more progress we get". According to Sinaga and Feranie (2017), who discussed critical thinking through writing-to-learn activities, students get the opportunity to read and review what they have written in analysing their evidence while making their claims in the process of writing. Their assertion that this situation naturally makes important contributions to the development of students' critical thinking processes has a common feature with this research: emphasizing the use of argument, evidence, and evaluation in the critical thinking process, which are presented as the causes of change in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The highest critical thinking skills were obtained on the students who were taught using the Differentiated Science Inquiry model combined with the mind map. Furthermore, Sinaga and Feranie (2017) found that variations in non-traditional writing tasks which included writing types, authentic audiences, text production, and content given to the students successfully increased their critical thinking skills. Zhou, Huang, and Tian (2013) stated that there were no significant differences in the total score, evaluation, and inference of the California Critical Thinking Skills Test between the task-based learning and lecturing teaching methods, but its findings provided an effective way for chemistry teachers to improve the students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Possible tasks to train students' critical thinking skills include exercising an analytical matter in which students are still required to collect their duties to the teacher by e-mail at a certain time. The concept of critical thinking can be seen as a way of thinking that develops from collecting some skills [24]. Critical thinking skills involve aspects of the accuracy and ambiguity of the information provided, including the ability to evaluate arguments based on specific criteria and evidence [25].…”
Section: Resultsmentioning
confidence: 99%